2005
DOI: 10.1021/jp049976e
|View full text |Cite
|
Sign up to set email alerts
|

Emission Properties of Manganese-Doped ZnS Nanocrystals

Abstract: We have performed steady-state and time-resolved fluorescence studies on undoped and Mn-doped ZnS nanocrystals with approximately 16 A diameter. While there is no band-edge emission, the intensity of the steady-state blue fluorescence from ZnS surface states decreases upon Mn incorporation, which gives rise to an orange emission. These results show that Mn incorporation competes very effectively with the donor-acceptor surface states for the energy transfer from the electron-hole pair excited across the band g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
159
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(177 citation statements)
references
References 39 publications
16
159
1
1
Order By: Relevance
“…Green PL emission from ZnS NPs at *535 nm is reported by Ye et al (2004) and it is assigned to elemental sulfur species present in the samples. Sapra et al (2005) have reported synthesis of ZnS:Mn NPs with DMF as the solvent and 1-thioglycerol as the capping agent and they have reported employing suitable organic agents. They have reported PL emission from the samples at 580 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Green PL emission from ZnS NPs at *535 nm is reported by Ye et al (2004) and it is assigned to elemental sulfur species present in the samples. Sapra et al (2005) have reported synthesis of ZnS:Mn NPs with DMF as the solvent and 1-thioglycerol as the capping agent and they have reported employing suitable organic agents. They have reported PL emission from the samples at 580 nm.…”
Section: Methodsmentioning
confidence: 99%
“…With decreasing particle size, 'quantum confinement effect' can be observed leading to a blue shift in the absorption spectrum of the particles (Brus 1998). Amongst others, ZnS is an II-IV semiconductor material and has a well-known wide direct band gap (3.71 eV at room temperature) and high exciton binding energy (*40 meV) (Brus 1998;Bhargava et al 1994;Bhargava 1996;Sapra et al 2005). It is therefore a potential candidate for optoelectronic applications in the short wavelength region (green, blue, UV) of the electromagnetic spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Different metal ions such as Cu, Mn, Pb, Co, Cd, Eu, and Sm doped with ZnS have been studied by many researchers because of their extensive photoluminescence (PL) properties [7]. Generally ZnS doped with these metal ions provide new opportunities as full-color luminescence in the UV-visible region [8][9][10][11][12]. Recent studies on Y ions incorporated into wide band gap semiconductor like ZnO [13,14] which resulted in significant increase in the optical properties, photocatalyst efficiency with improved stability of ZnO nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the effect of Mn on the radiative centers of ZnS microbelts are investigated by analysing the PLE spectra shown in Figure 4. In fact, excitation pathway for the emission of Mn 2+ in the microbelts has two ways, namely the energy transfers directly from the ZnS host and another from the radiative defects to the 3d states of Mn 2+ [7]. The PLE measurements monitored at the emission wavelength of 570 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Email: nghiaaist@gmail.com https//doi.org/ 10.25073/2588-1124/vnumap.4212 tunable optical properties, could be obtained [5][6][7]. Among them, Mn-doped ZnS nanocrystals have been receiving much attention due to their promising application in optoelectronic devices [8].…”
Section: Introductionmentioning
confidence: 99%